Sphenopalatine ganglion stimulation: a comprehensive evaluation across diseases in randomized controlled trials - Qin, Lingli; Chen, Dian; Li, Xian; Gao, Yue; Xia, Wanying; Dai, Hanxi; Qiu, Linjie; Yang, Jinsheng; Zhang, Lu (Frontiers in Neurology, 2024)
Background This paper aims to bridge this gap by conducting a comprehensive review and analysis of existing literature on SPGs across various medical conditions. Methods This study meticulously constructed a comprehensive database through systematic computerized searches conducted on PubMed, Embase, CNKI, Wanfang, VIP, and CBM up to May 2022. The inclusion criteria encompassed RCTs published in either Chinese or English, focusing on the therapeutic applications of SPGs for various medical conditions. Both qualitative and quantitative outcome indicators were considered eligible for inclusion. Results This comprehensive study reviewed 36 publications, comprising 10 high-quality, 23 medium-quality, and 3 low-quality articles. The study investigated various diseases, including AR, IS, CH, PTN, PCSO, RFP, CTTH, as well as the analysis of LF-SPGs in CCH and the impact of SPGs on NNCF. SPGs demonstrate efficacy in the treatment of AR. Regarding the improvement of RQLQ scores, SPGs are considered the optimal intervention according to the SUCRA ranking. Concerning the improvement in TNSS, CA-TCM holds a significant advantage in the SUCRA ranking and is deemed the best intervention. In terms of increasing ER, SPGs outperformed both CA and WM (P <0.05). In the context of SPGs treatment for IS, the results indicate a significant improvement in the three-month outcomes, as evaluated by the mRS in the context of CCI (P <0.05). In the treatment of CH with SPGs, the treatment has been shown to have a statistically significant effect on the relief and disappearance of headaches (P <0.05). The impact of SPGs on NNCF reveals statistically significant improvements (P <0.05) in NAR, NCV, eNO, SP, VIP and NPY. SPGs treatments for PCSO, RFP, and CTTH, when compared to control groups, yielded statistically significant results (P <0.05). Conclusion SPGs demonstrate significant effectiveness in the treatment of AR, IS, and CH. Effective management of CCH may require addressing both autonomic dysregulation and deeper neural pathways. However, additional high-quality research is essential to clarify its effects on NNCF, PTN, PCSO, RFP, and CTTH.